1975
DOI: 10.1530/acta.0.0780574
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone-Binding Proteins: In Vitro Binding and Biological Activity of Different Steroidal Ligands

Abstract: Progesterone-binding proteins from human, rabbit, sheep and guinea pig myometrial cytosol, all induced with oestradiol, as well as from pregnant guinea pig myometrium and plasma were investigated. The physico-chemical properties of the oestradiol-induced binding proteins were very similar in all the species studied. In all, 63 steroids were tested for their ability to compete with tritiated progesterone for the binding sites on these six proteins and their relative affinities were determined. The studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
2

Year Published

1979
1979
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(40 citation statements)
references
References 0 publications
4
34
2
Order By: Relevance
“…Yet, it acted as a mitogen in MCF-7 cells. It has been widely established that estrogens induce PR expression not only in female reproductive tissues but also in normal and malignant mammary epithelial cells (Kontula et al, 1975;Nardulli et al, 1988;Wei et al, 1988). In sharp contrast, the present study revealed significantly decreased PR-A and PR-B expression in HOSE or OVCA cell lines following exposure to an estrogen.…”
Section: Discussioncontrasting
confidence: 80%
“…Yet, it acted as a mitogen in MCF-7 cells. It has been widely established that estrogens induce PR expression not only in female reproductive tissues but also in normal and malignant mammary epithelial cells (Kontula et al, 1975;Nardulli et al, 1988;Wei et al, 1988). In sharp contrast, the present study revealed significantly decreased PR-A and PR-B expression in HOSE or OVCA cell lines following exposure to an estrogen.…”
Section: Discussioncontrasting
confidence: 80%
“…If this hypothesis were true, then human progesterone receptor would have more such determinants in common with rabbit receptor than the guinea pig and the rat receptor. Similarity in ligand specificity between human and rabbit progesterone receptors has been reported (8). These crossreactions with the corresponding receptor from various species are similar to observations made for estrogen receptors (5); however, a difference resides in the fact that antirabbit progesterone antibodies do not interact with a nonmammalian receptor (from chicken oviduct) whereas the anti-calf estrogen receptor antibodies do interact with the chicken oviduct estrogen receptor (3).…”
Section: Methodssupporting
confidence: 74%
“…The [3H]R5020 specific binding was sensitive to proteases and sulfhydryl re agents but not to nucleases, indicating ste roid binding stability depended on protein and sulfhydryl group integrity. Furthermore, the general pattern of efficacy shown in the competition studies parallels the patterns observed for progesterone receptors of both rabbit and human uterus [Kontula et al, 1975;Laumas and Kasid, 1980]. The most potent competitors (R5020, norgestrel.…”
Section: Discussionsupporting
confidence: 58%